Peran Pemimpin Informal Etnis Suku Bajau Dalam Pengembangan Pariwisata Di Gugusan Kepulauan Derawan Kabupaten Berau - Dian Yusril Alamsyah; Mohammad Taufik; Letizia Dyastari (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
This study aims to analyze the role of informal leaders of the Bajau ethnic group in the development of tourism in the Derawan Archipelago, Berau Regency. Informal leaders within the Bajau community play a crucial role in mobilizing the community to participate in the tourism sector, including managing tourist destinations, enhancing community skills, and preserving natural and cultural heritage. The research employs a qualitative approach, collecting data through in-depth interviews with informal leaders, community figures, and local residents. The findings indicate that Bajau informal leaders significantly motivate community involvement in tourism development, despite challenges such as limited training and formal education. As facilitators, these leaders create effective deliberation forums to voice community aspirations in tourism management. Additionally, they act as mobilizers, successfully encouraging active participation in managing and developing marine tourism, although infrastructure limitations and inadequate tourism facilities pose challenges. Informal leaders of the Bajau ethnic group in the Derawan Archipelago hold a vital role in tourism development by fostering local cultural diversity, improving the community’s economy, and promoting sustainable environmental management. To optimize this role, support is needed to enhance human resource capacity, infrastructure development, and more supportive regulations for the local tourism sector.Authors must supply a structured abstract in their submission, which includes; Purpose (mandatory), Design/methodology/approach (mandatory), Findings/results (mandatory), Research limitations/implications (if applicable), Practical implications (if applicable), Social implications (if applicable), Originality/value (mandatory).